Ethical Trade and Public Enterprise: Controlling Consumption in Ontario's Liquor Market. Issue 2 (July 2015) - Fridell, Gavin
This article examines the Liquor Control Board of Ontario (LCBO) as a form of ethical trade. Its unique public mandate, rooted in "con trolling consumption" and semi-monopoly, has been central to its relative success as well as its general disregard by Corporate Social Responsibility (CSR) and ethical trade advocates, who focus on the actions of private corporations and individual consumers. Exploring the political significance of this oversight, its gaps and slippages, this article argues that the LCBO would do very well by standard CSR metrics, while also transcending them in several ways. The LCBO contributes billions of dollars to the public purse, acts as a form of "hidden developmental state, " negotiates prices with suppliers on the basis of "fair and equitable treatment, " and employs a unionized workforce with comparatively strong labour conditions. Recognizing this offers both a challenge to the dominant understandings of CSR, and the fantasies of a "harmonious market society, " while pointing to a wider perspective on a more transformative political vision of ethical trade.